The Effect of Brand Image and Product Quality on Fast Food Consumer Loyalty in East Java Province: Pengaruh Citra Merek Dan Kualitas Produk Terhadap Loyalitas Konsumen Makanan Cepat Saji di Provinsi Jawa Timur - Melania, Dewi Riski; Sukmono, Rita Ambarwati (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of brand image and product quality on consumer loyalty at McDonald's in East Java. This study uses a quantitative approach with a questionnaire survey method. The method of determining the sample is simple random sampling. The sample used is 100 respondents who have bought McDonald's products in East Java. The data analysis used is outer model test and the inner model test on the Smart PLS software application. The results of this study indicate that there is an influence of brand image on consumer loyalty McDonald's in East Java, With the results of a good brand reputation indicator which dominantly reflects the brand image variable and the less dominant loyalty indicator reflects the brand image variable. There is an effect of product quality on consumer loyalty McDonald's in East Java, with the result that the dominant flavor variant indicator reflects the product quality variable and the less dominant product shelf life indicator reflects the product quality variable.